2021
DOI: 10.3390/cells11010067
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating T Cell and B Cell Responses to SARS-CoV-2 in Humans: Gaining Insights into Protective Immunity and Immunopathology

Abstract: The SARS-CoV-2 pandemic is an unprecedented epochal event on at least two fronts. Firstly, in terms of the rapid spread and the magnitude of the outbreak, and secondly, on account of the equally swift response of the scientific community that has galvanized itself into action and has successfully developed, tested and deployed highly effective and novel vaccines in record time to combat the virus. The sophistication and diversification of the scientific toolbox we now have at our disposal has enabled us to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 129 publications
(273 reference statements)
0
6
0
4
Order By: Relevance
“…It is unclear how these associations can be reconciled with earlier observations on the association of a strong T-cell response with mild COVID-19 and a weak one with severe disease; Kusnadi et al , 45 at least, propose that a robust memory CD8 + T-cell response in severe COVID-19 may be contributory toward prevention against re-exposure. It may also be that in certain patients T cells may themselves promote disease pathogenesis, 46 which might convolute association data. In contrast, Zheng et al 47 found the frequency of the non-exhausted CD8 + T-cell subset to be reduced in those with severe infection.…”
Section: T-cell Control Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…It is unclear how these associations can be reconciled with earlier observations on the association of a strong T-cell response with mild COVID-19 and a weak one with severe disease; Kusnadi et al , 45 at least, propose that a robust memory CD8 + T-cell response in severe COVID-19 may be contributory toward prevention against re-exposure. It may also be that in certain patients T cells may themselves promote disease pathogenesis, 46 which might convolute association data. In contrast, Zheng et al 47 found the frequency of the non-exhausted CD8 + T-cell subset to be reduced in those with severe infection.…”
Section: T-cell Control Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Основной функцией, которую выполняют Т-лимфоциты, является целенаправленная эрадикация инфицированных клеток. Т-клетки также оказывают критически важную помощь В-лимфоцитам для развития патоген-специфичного гуморального иммунного ответа [1]. Во время пандемии COVID-19 разработана концепция «клеточной сенсибилизации без сероконверсии» [2].…”
Section: клеточный иммунный ответ на острую инфекцию Sars-cov-2unclassified
“…Способность SARS-CoV-2 адаптироваться к среде организма хозяина и довольно быстро эволюционировать стала проблемой для вакцинологов. Требуется разработка вакцин, нацеленных на более консервативные вирусные детерминанты (например, нуклеопротеин), где мутации могут сильно нарушить репликацию вируса [1].…”
Section: т-клеточные ответы у реципиентов вакцины против Covid-19 схо...unclassified
See 2 more Smart Citations